Varieties of Religious Authority Changes and Challenges in 20th Century Indonesian Islam - Azra, Azyumardi; Kaptein, Nico J. G.; van Dijk, Kees (ISEAS Publishing, 2010)
The twentieth century was a fascinating period of profound political, social and economic changes in Indonesia. These changes contributed to the diversification of the religious landscape and as a result, religious authority was redistributed over an increasing number of actors. Although many Muslims in Indonesia continued to regard the ulama, the traditional religious scholars, as the principle source of religious guidance, religious authority has become more diffused and differentiated over time. The present book consists of contributions which all deal with the multi-facetted and multidimensional topic of religious authority and aim to complement each other. Most papers deal with Indonesia, but two dealing with other countries have been included in order to add a comparative dimension. Amongst the topics dealt with are the different and changing roles of the ulama, the rise and role of Muslim organizations, developments within Islamic education, like the madrasa, and the spread of Salafi ideas in contemporary Indonesia